Scholastic Achievement and the Diglossic Situation in a Sample of Primary-School Students in Ceuta - José María Roa Venegas (Universidad Autónoma de Baja California, 2006)
In this paper we have tried to compare, in a sample of Spanish first and second-grade students whose mother tongue is Dhariya, with those of other students of the same level, but whose mother tongue is Spanish, the achievement levels in some functions and skills related to the maturity needed for learning at school. The results showed significant differences between subjects speaking the different vernaculars as a first language. Dhariya-speaking students obtained lower scores on skills such as visual-auditory, memory, elemental concepts and language dysfunctions. We can reasonable assume the importance which conceptual development, so strongly associated with the mastery of the language used, could have on the student's scholastic achievement.